Cost-effectiveness analysis and budget impact analysis of next-generation sequencing panel including BRCA1 and BRCA2 genes for women diagnosed with non-metastatic breast cancer in Brazil - Couto, Henrique Lima; Rahel, Rosemar Macedo de Souza; Gargano, Ludmila Peres; Zanghelini, Fernando; Silva filho, Agnaldo Lopes da; Hassan, Augusto Tuf; Rodrigues, Angélica Nogueira; Coelho, Bertha Andrade (Mastology, 2026)
Objective: This study aimed to estimate both the cost-effectiveness and budget impact of using next-generation sequencing panels with genetic counselling to detect BRCA1/2 mutations in women diagnosed with non-metastatic breast cancer and compare to no genetic testing, from the perspective of the Brazilian Public Health System. Methods: A hybrid economic model (decision tree plus Markov model) simulated costs and outcomes over a 10-year horizon of next-generation sequencing panels with genetic counselling to identify BRCA1/2 pathogenic variants in women diagnosed with non-metastatic breast cancer. The eligible population was estimated using the epidemiological method with national data identified in the literature. We estimated both the incremental cost-effectiveness ratio per quality-adjusted life year (QALY) gained and the budget impact of adding next-generation sequencing panels plus genetic counselling to identify pathogenic variants in BRCA1/2 in women diagnosed with non-metastatic breast cancer. Results: Genetic testing for BRCA1/2 mutations combined with genetic counselling showed an incremental benefit of 0.044 QALYs gained at an additional cost of R$ 3.314,83 compared to no genetic testing and genetic counselling, resulting in an incremental cost-effectiveness ratio of R$ 75.961,11 per QALY gained. Considering the expected number of women, the cumulative budget impact over five years with the availability of genetic testing for BRCA1/2 and genetic counselling would be R$ 31.104.761,08, based on the current scenario (without BRCA1/2 test and genetic counselling). Conclusion: Genetic testing for BRCA1/2 mutations combined with genetic counselling was cost-effective from the Brazilian Public Health System perspective, with an incremental cost-effectiveness ratio value below the established willingness-to-pay threshold of R$ 120,000.00/QALY.